2018
DOI: 10.1371/journal.pone.0194264
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of Ethanol and Taurine on frontal cortex absolute beta power before and after exercise

Abstract: Ethanol (ET) is a substance that modulates the Central Nervous System (CNS). Frequently, ET intake occurs combined with energy drinks, which contain taurine (TA), an important amino acid found in the body (i.e brain and muscles). Although TA administration has been used in the improvement of physical performance, the impact of TA, ET and exercise remains unknown. This study aimed to analyze the acute effect of 6g of Taurine (TA), 0.6 mL∙kg-1 of Ethanol (ET), and Taurine combined with Ethanol (TA+ET) ingestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…Chronic supplementation with low doses of taurine was shown to improve learning in old mice and performance on a spatial task in a water pool (Trenkner et al 1998) and in the Y maze test (Singh et al, 2023). It also allowed restoration of plasticity damaged after alcohol administration and in a mouse model of Alzheimer's disease, in addition to improving visual discrimination impaired in old mice (Kim and Cha 2014;Paulucio et al, 2018). The present paper shows, for the rst time, the positive in uence of TS on experience-dependent learning-associated plasticity in the somatosensory cortex.…”
Section: Discussionsupporting
confidence: 52%
“…Chronic supplementation with low doses of taurine was shown to improve learning in old mice and performance on a spatial task in a water pool (Trenkner et al 1998) and in the Y maze test (Singh et al, 2023). It also allowed restoration of plasticity damaged after alcohol administration and in a mouse model of Alzheimer's disease, in addition to improving visual discrimination impaired in old mice (Kim and Cha 2014;Paulucio et al, 2018). The present paper shows, for the rst time, the positive in uence of TS on experience-dependent learning-associated plasticity in the somatosensory cortex.…”
Section: Discussionsupporting
confidence: 52%
“…Abnormally increased beta band power, especially at frontal electrode positions, has been reported for adult alcoholics [38], adult patients with panic disorders and agoraphobia [39], and older adults with cognitive decline [40]. Increased beta band power (at frontal electrodes) has also been reported after the administration of ethanol [41]. Abnormal beta band power is often considered a neurophysiological index of (abnormal) cortical hyperexcitability and disinhibition [42], which might indicate a deteriorated balance of inhibition and excitation in maintaining cortical homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have demonstrated that exercise can protect against drinking-induced injury in the central nervous system (Coiro et al 2007;Paulucio et al 2018); however, its mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%